2015
DOI: 10.1083/jcb.201504006
|View full text |Cite
|
Sign up to set email alerts
|

Live-cell observation of cytosolic HIV-1 assembly onset reveals RNA-interacting Gag oligomers

Abstract: Analysis of the cytosolic HIV-1 Gag fraction in live cells via advanced fluctuation imaging methods reveals potential nucleation steps before membrane-assisted Gag assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
108
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(125 citation statements)
references
References 83 publications
16
108
1
Order By: Relevance
“…In support of this idea, crosslinking experiments performed in living cells revealed that the major Gag-interacting RNAs in cytosol are host ncRNAs, particularly tRNAs and 7SL RNA (Kutluay et al 2014). Although the tRNA crosslinks were largely dependent on Matrix, a Gag domain dispensable for forming oligomers, crosslinks to most other host RNAs were strongly reduced by mutations in nucleocapsid (NC), a domain important for oligomer formation (Kutluay et al 2014;Hendrix et al 2015).…”
Section: B Cmentioning
confidence: 79%
See 2 more Smart Citations
“…In support of this idea, crosslinking experiments performed in living cells revealed that the major Gag-interacting RNAs in cytosol are host ncRNAs, particularly tRNAs and 7SL RNA (Kutluay et al 2014). Although the tRNA crosslinks were largely dependent on Matrix, a Gag domain dispensable for forming oligomers, crosslinks to most other host RNAs were strongly reduced by mutations in nucleocapsid (NC), a domain important for oligomer formation (Kutluay et al 2014;Hendrix et al 2015).…”
Section: B Cmentioning
confidence: 79%
“…There is much evidence that RNA binding promotes Gag oligomerization (Campbell and Vogt 1995;Rein et al 2011;Hendrix et al 2015); however, the identities of the responsible RNAs remain unknown. As noted previously (Eckwahl et al 2015;Eckwahl et al 2016), newly synthesized RNAs that have not bound their usual protein partners may be more likely than components of mature RNPs to have the 15-16 nt of protein-free RNA that is needed for Gag multimerization in vitro (Campbell and Rein 1999;Ma and Vogt 2002).…”
Section: B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Tight confinement further distorts the distribution, because this boundary condition excludes the largest step sizes. The artifacts introduced by confinement and in-frame motion were not encountered in previous applications of image correlation spectroscopy, because those experiments focused on slow motion (26,(31)(32)(33)(34), or else minimized pixel dwell time, as in raster image correlation spectroscopy (29). On the other hand, here in the regime of fast, confined motion, the two independent effects of blur and confinement manifest themselves as two independent diffusion-coefficient measurement biases.…”
Section: Introductionmentioning
confidence: 96%
“…All of these methods compute the correlation function of an entire fluorescence imaging movie instead of relying on localization and tracking, and like fluorescence correlation spectroscopy, these powerful image correlation approaches can be extended to measure 2D maps of heterogeneous diffusion (18,26) and very fast diffusion (27). Particle image correlation spectroscopy measures diffusion dynamics by computing a similar correlation function from data that have already been processed with the Gaussian localization used in SPT and other methods (28).…”
Section: Introductionmentioning
confidence: 99%